Frequency and associated factors of mask-induced acne among healthcare workers - Abbas Ali, Kholood; Majeed Sqban , Zainab (Diyala Journal of Medicine, 2024)
Background: Mask-induced acne, also known as maskne, is a skin condition that has become increasingly prevalent during the COVID-19 pandemic. The prolonged use of facial masks has been found to cause skin irritation, inflammation, and the development of acne. Healthcare workers are at an increased risk due to their prolonged and consistent use of facial masks during their work. Objective: To investigate the occurrence and identify risk factors of mask induced acne among health care workers. Patients and Methods: This cross-sectional study included 115 healthcare workers at Al_Imamain Al_Kadhumain Medical city who wore the mask daily. Collected data include demographic characteristics (age, sex, and occupation), mask-wearing data include the type of mask worn, the pattern of mask use (disposable or reusable mask), time spent wearing masks over the years, the daily duration of mask usage, and specifics regarding participants' acne, encompassing the type and facial location of the acne, as well as accompanying symptoms (itching, dryness, oiliness, moisture, warmth, and excessive facial sweating), and factors that exacerbate the condition, were all considered in the study. Results: Out of 115 included subjects 37 (32.17%) were suffering from new-onset mask induce acne. There were 10 men and 27 women. The mean age was 35.5±7.3 years (range: 24-47). The vast majority of the included participants (81.08%) were wearing surgical masks. The duration of mask use in about three-fourths of patients was ≥ one year. About three-fourth of patients were using reusable mask. Pustules were the most common lesion, accounting for two-thirds of the participants, followed by comedones (37.83%). The most common site was cheeks (75.67%), followed by the chin (48.65%). Stress was the most common aggravating factor occurred in 37.84% of the participants, followed by high-glycemic diet and hot weather (27.03% each). Conclusion: Female, prolonged duration of mask use and wearing reusable masks could be associated with the development of maskne. Stress and a glycemic diet could aggravate the lesion associated with maskne.